The use of coffee for the prevention of ileus following abdominal surgery: A review of the current evidence - Güngördük, Kemal; Gülseren, Varol; Özdemir, İsa Aykut (Galenos Publishing House, 2022)
Postoperative ileus (POI) is a form of intestinal paralysis that is seen especially after surgical procedures performed by entering the abdominal cavity. POI is common, particularly after abdominal surgery, with an incidence of 8-30%. The initial phase of postoperative paralytic ileus is treated with decompression using a nasogastric tube to correct electrolyte imbalances, with analgesia applied as needed. Prokinetic compounds have been used to prevent ileus and control pain (such as serotonin receptor antagonists, neostigmine, alvimopan, and ghrelin agonists), along with early mobilization, minimally invasive surgery, early introduction of solid food into the diet, thoracic epidural analgesia, and fluids. Coffee has been shown to accelerate postoperative bowel movements. However, despite extensive research on the physiological impacts of coffee, little is acknowledged regarding how it affects the gut. Coffee increases colonic motility within 4 min of consumption. In the postoperative period, the number of intestinal vocals heard by auscultation of intestinal vocals, first gas and first defecation times of patients who consume coffee are smaller/shorter than patients who do not consume coffee. Patients who drink coffee also have shorter hospital stays.
Keywords: Paralytic Ileus; Postoperative Ileus; Surgery; Gynecological Malignancy